Molecular Detection of Cucumber Mosaic Virus and Tobacco Mosaic Virus Infecting African Nightshades (Solanum scabrum Miller) - S. L. Kimaru; D. C. Kilalo; W. M. Muiru; J. W. Kimenju; C. R. Thuku (International Journal of Agronomy)
The two viruses cucumber mosaic virus (CMV) and tobacco mosaic virus (TMV) are among the major viruses that constrain the production of African nightshade (ANS). The ANS provides high proportions of micronutrient content and has medicinal, economic, and agronomic benefits. In this study, we utilized molecular methods to detect these viruses present in ANS at two locations in Kenya: Kisii and Kakamega counties. Ribonucleic acid (RNA) was extracted from leaves of ANS plants exhibiting viral symptoms and sequenced on the Illumina MiSeq platform for phylogenetic studies. The isolates were grouped based on nucleotide and sequence identity. We detected two isolates of CMV and one isolate of TMV in ANS samples. The isolate sequences have been deposited in the GeneBank to obtain accession numbers. Cucumber mosaic virus nucleotide sequence closely resembled the Kirinyaga isolates in Kenya classified in subgroup I. Tobacco mosaic virus phylogenetic studies revealed close resemblance of isolates KY810785.1 from Britain and AF273221.1 from the USA in clade 1 based on nucleotide and amino acid sequences. This is an indication that the virus is widely distributed across the world. Detection of these two viruses in Kenya suggests that they are prevalent in crop-growing regions and the germplasms. African nightshade could also act as a virus reservoir infecting other plants. This study will inform management options to prevent virus epidemics and be in control of vectors.